Sistem Pendukung Keputusan Pemilihan Kualitas Kedelai Sebagai Bahan Baku Tahu Menggunakan Metode TOPSIS - Larissa Navia Rani (Riset Sinergi Indonesia (RISINDO), 2022)
Soybeans are a plant that has a high level of protein, and soy sauce is also widely used by producers as raw ingredients for tofu, tempe, various, processed foods, and other beverages. the various types of soybeans make business perpetrators confused about determining the best quality of soybeans. therefore, to speed up the selection of the best-quality soy needed a decision support system. the method used in the support systems of this decision is the technique for order preference by similarity to the ideal solution (TOPSIS), which is chosen because this method is able to select the best alternatives from the existing alternatives. using this system is expected to be able to assist the business perpetrators in making decisions when choosing the type of soybeans that have the best quality.